Emergence of Nepalese English: A Case of Short Stories - Bhattarai, Prakash (Journal of NELTA Gandaki, 2022)
The wide use of English language around the globe in the recent decades has generated different varieties of English language with their own distinctive features; one of such varieties is Nepalese English. Several English literary texts written by Nepalese writers along with different other factors are contributing to establish Nepalese English as a different variety of English. Analyzing six English short stories written by three Nepali writers, this article examined the Nepalese English used in the short stories to find out their distinctive features. The stories were analyzed and interpreted using interpretative research paradigm. After the analyses, it was found that there is code mixing and code switching (Nepali and English) in the stories; Nepali names are given to the characters to give real flavor of Nepaleseness and the short stories reflect the Nepalese societies in terms of the condition of women, development, education and employment.